Sistemizacija, organizacija, razvoj in uporaba podatkovne baze urnih postavk metereološkega leta za območje Damaska - Skeiker, Kamal (Strojniški vestnik, 2000)
The weather data for the Damascus zone for the years 1970 through 1993 as measured by the Department of metereology were obtained, examined and reconditioned. Using these measured data, a Reference Metereological Year "RMY" Database was organized and developed according to the following patterns: 1-monthly average of hourly weather data, 2-hourly weather data, 3-daily sunshine hours. The LOS-A0 computer program for the dynamic analysis of heat transfer in buildings was modified for use according to the working conditions and weather seasons in Syria. It was provided with an hourly weather database of the first pattern. This last version was developed, and a new version CLIMA, in which the calculation is carried out of an optional period during the year, was obtained. The computer program CLIMA was provided with an hourly database of the second pattern. These two versions were used to study an enclosure as an example. After detailed analysis of the calculated results obtained by each of the two mentioned versions, the computer program CLIMA was chosen.
Keywords: podatki metereološki; baze podatkov; programi računalniški; analize dinamične; obdelava podatkov; vreme; weather; Damask